The Supraclavicular Artery Perforator Flap: A Comparative Study of Imaging Techniques Used in Preoperative Mapping - Sheriff, Hemin Oathman; Mahmood, Kawa Abdullah; Hamawandi, Nzar; Mirza, Aram Jamal; Hawas, Jawad; Moreno, Esther Granell; Clavero, Juan Antonio; Hankins, Christopher; Masia, Jaume (Journal of Reconstructive Microsurgery, 2018)
Background The supraclavicular artery flap is an excellent flap for head and neck reconstruction. The aim of this study is to assess imaging techniques to define the precise vascular boundaries of this flap.Methods Six imaging techniques were used for supraclavicular artery mapping in 65 cases; handheld Doppler, triplex ultrasound, computed tomography angiography, magnetic resonance angiography, digital subtraction angiography, and indocyanine green angiography. We checked the site of the perforators, the course of a supraclavicular artery, and anatomical mapping of the supraclavicular artery.Results Handheld Doppler identified perforators' sites in 80% of the cases but showed no results for the course of the vessel. Triplex ultrasound identified the site of perforators in 52.9%, and partial mapping of the course of a supraclavicular artery in 64.7% of the cases. Computerized tomography angiography showed the site of perforators in 60%, and the course of supraclavicular artery completely in 45%, and partially in an additional 30%of the cases examined. Magnetic resonance angiography showed negative results for all parameters. Digital subtraction angiography showed the partial course of a supraclavicular artery in 62.5%, but showed no perforators. Indocyanine green angiography showed the site of perforators in 60% and a partial course of supraclavicular artery distal to perforators in 60%.Anatomical mapping of the vessel was possible with computerized tomography angiogram completely in 45%, and partially in 30%, and was also possible with indocyanine green angiography partially in 60%.Conclusion Computerized tomography angiography showed best results in the mapping of the supraclavicular artery, but with an inability to define the perforator perfusion territories, and also with risks of irradiation, while indocyanine green angiography is a good alternative as it could precisely map the superficial course of the artery and angiosomes, with no radiation exposure.
Keywords: imaging; mapping; supraclavicular